دعاوى أثر التعاليم البوذية في التصوف الإسلامي: دراسة تحليلية لنظريات المستشرقين = (Claims on the influence of Buddhist teaching on sufism: an analytical study on views of orientalists) - Ahmad, Masitoh (IIUM Press, 2023)
The article aims at discussing views of some orientalists on Islamic Mysticism. It will also analyse their claims on the influence of the teaching of Buddhism on the formation and the development of Sufism. The study also briefly touches the purposes, driving factors and the methods of Orientalists in studying and conducting research on Islamic culture in general and Sufism in particular. The study utilises methods of qualitative in which library research and analytical methods are applied. The study concludes that Islamic Sufism is neither alien to Islam and nor the product of the influence of a Buddhist culture. Rather, it is the product of asceticism that originated in Islam, and its sources and roots are in the Qur‘an and Sunnah. Even though there is an apparent similarity between the mystical annihilation (al-fanā‘ al-ṣūfī) and Buddhist nirvana, it does not indicate that al-fanā derives from a Buddhist source, as there are essential differences between the two. Similarity is a common phenomenon in Sufism known as the ―unity of the Sufi experience. This is because Sufism is mainly related to feeling and conscience. What one human soul achieves through struggle and spiritual exercise may be achieved by another, without any connection between them. The orientalists‘ claims of the influence of Buddhist teachings on Islamic Sufism, given the similarity between the Sufi and Buddhist approaches to attaining al-ḥaqīqah and al-ma‘rifah, is invalid, as the similarity and the resemblance between the two schools of thought do not prove that one of them was influenced by the other.